MAKNA PEMAKAIAN BENTUK -LA DALAM BAHASA PALEMBANG - Astuti . (Universitas Muhammadiyah Malang, 2015)
MAKNA PEMAKAIAN BENTUK -LA DALAM BAHASA PALEMBANG AstutiSMP PGRI Srikaton Musi Rawas Sumatera Selatanaaspicces@yahoo.com Abstrak: Penelitian ini bertujuan untuk mendeskripsikan makna pemakaian bentuk -la dalam bahasa Palembang. Penelitian ini menggunakan metode deskriptif, adapun jenis penelitian adalah kualitatif. Sumber data dalam penelitian in berupa tuturan lisan berbahasa Palembang yang peneliti peroleh dari komunikasi antaranggota komunitas masyarakat Palembang. Dalam hal ini subjek penelitian adalah masyarakat Desa Tribina Suro, SUM-SEL. Data dalam penelitian ini berupa kata, frase, klausa, dan tata kalimat bentuk -la dalam bahasa Palembang. Hasil penelitian ini adalah deskripsi Makna bentuk -la dapat dikategorikan menjadi empat makna, yaitu bentuk -la sebagai makna umpatan, bentuk -la sebagai makna pemberitahuan, bentuk -la sebagai makna perintah, dan bentuk -la Sebagai makna Penekanan. Kata Kunci: analisis, bentuk, makna. ABSTRACT: This research is descriptive study about variation of particle -la in Palembang language. The problems here area (1) How is the descrition of form -la in Palembang language? (2) How is the descriptive meaning of form -la in Palembang language? (3) How is the descriptive meaning of form -la in Palembang language grammer? (4) How is correlation of using form -la with sense value and local cultural understanding in Palembang? Generally, the aim of is to describe variation of form -la in Palembang language. Theory that is used here is morphology ang semantic. Morphology theory is a science that studies about words form and the influense of form changes toward meaning groups. The approach of the research used qualitative. It is descriptive method that it can be understood as procedure series that is used in the effort of problem solving that is investigated by explaining or describing meaning in the use of particle -la in Palembang language based on the facts invisibly or as they are. The data of the research is forms and grammars in using particle -la in Palembang society for communication. Data subject in this study is community of residents in Suro, Palembang, shouth Sumatra Selatan. The result is in the description of form -la meaning can be categoriozed to be four meaning; they are, form -la as verbal abuse, form -la as notification. Also, form -la is as command, and form -la is as compression. Key Words: analysis, form, meaning.